2020
DOI: 10.1038/s41598-020-68485-2
|View full text |Cite
|
Sign up to set email alerts
|

A modification of a traditional Ethiopian maize store for solar powered ambient drying to reduce post-harvest losses

Abstract: A gombisa is a traditional Ethiopian structure widely used for maize storage over several months. It lacks adequate ventilation for timely moisture removal, which promotes mold development and aflatoxin production. In this study, a traditional gombisa was compared to one modified by installing a solar powered fan to provide forced ambient air ventilation during daytime. Approximately 900 kg of moist ear maize were loaded into each structure and samples from selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For bulk drying of maize, its wall is made from permeable wood material. Drying of maize occurs exclusively by wind where wind coming through the walls defuses the moisture from the maize surface (Roman et al, 2020). Bereka et al (2022) reported that more than 80% of respondents from Jimma area World Mycotoxin Journal 0 (2023) 1-16 use gombisa for maize storage.…”
Section: Postharvest Practices and Mycotoxin Contaminationmentioning
confidence: 99%
See 4 more Smart Citations
“…For bulk drying of maize, its wall is made from permeable wood material. Drying of maize occurs exclusively by wind where wind coming through the walls defuses the moisture from the maize surface (Roman et al, 2020). Bereka et al (2022) reported that more than 80% of respondents from Jimma area World Mycotoxin Journal 0 (2023) 1-16 use gombisa for maize storage.…”
Section: Postharvest Practices and Mycotoxin Contaminationmentioning
confidence: 99%
“…The common storage structures are influenced by external environmental conditions, such as moisture migration and oxygen permeability. This enables fungal growth and insect infestation (Garbaba et al, 2018a;Roman et al, 2020). In addition, these structures are prone to internal moisture condensation which also helps fungal growth (Roman et al, 2020).…”
Section: Postharvest Practices and Mycotoxin Contaminationmentioning
confidence: 99%
See 3 more Smart Citations